5-ALA-guided tumor resection during awake speech mapping in gliomas located in eloquent speech areas: Single-center experience - Goryaynov, Sergey A.; Buklina, Svetlana B.; Khapov, Ivan V.; Batalov, Artyom I.; Potapov, Alexander A.; Pronin, Igor N.; Belyaev, Artem U.; Aristov, Andrey A.; Zhukov, Vadim U.; Pavlova, Galina V.; Belykh, Evgenii (Frontiers in Oncology, 2022)
Background. Achieving maximal functionally safe resection of gliomas located within the eloquent speech areas is challenging and there is lack of literature on combined use of 5-aminolevulinic acid(5-ALA)-guidance and awake craniotomy. Objective. To describe our experience with simultaneous use of 5-ALA fluorescence and awake speech mapping in patients with left frontal gliomas located within the vicinity of eloquent speech areas. Materials and methods. Prospectively collected database of patients was reviewed. 5-ALA was administered at a dose of 20 mg/kg 2 hours prior to operation and operating microscope in a BLUE 400 mode was used to visualize fluorescence. All patients underwent surgery using “asleep-awake-asleep” protocol with monopolar and bipolar electrical stimulation to identify proximity of eloquent cortex and white matter tracts and to guide safe limits of resection along with fluorescence guidance. Speech function was assessed by the trained neuropsychologist before, during and after surgery. Results. In 28 patients operated with cortical mapping and 5-ALA guidance (12 Grade 4, 6 Grade 3 and 10 Grade 2 gliomas), Brocka’s area was identified in 23 and Wernicke are in 5 cases. Fluorescence was present in 14 cases. Six tumors had residual fluorescence due to the positive speech mapping in the tumor bed. Transient aphasia developed in 14 and permanent in 4 patients. In 6 patients operated with cortical and subcortical speech mapping and 5-ALA guidance (4 Grade 4, 1 Grade 3 and 1 Grade 2 gliomas), cortical speech areas were mapped in 5 and subcortical tracts encountered in all cases. In all cases resection was stopped despite the presence of residual fluorescence due to speech mapping findings. Transient aphasia developed in 6 and permanent in 4 patients. In patients with Grade 2-3 gliomas targeted biopsy of focal fluorescence areas lead to upgrading the grade and thus more accurate diagnosis. Conclusion. 5-ALA-guidance during awake speech mapping is useful in augmenting the extent of resection for infiltrative high-grade gliomas, identifying foci of anaplasia in non-enhancing gliomas, while maintaining safe limits of functional resection based on speech mapping. Positive 5-ALA fluorescence in diffuse Grade 2 gliomas may be predictive of more aggressive disease course.